187k views
3 votes
-4(x - 2) - 3x = 2(5x - 7) + 6

After distributing and combining like terms, this problem should read:

7 - 8x = -10 + 8x

-15x = 10x - 8

8x - 6 = 7x - 3

-11x + 8 = 10x - 8

-7x + 8 = 10x - 8

1 Answer

0 votes

Answer: last option.

Explanation:

To apply the Distributive property, remember that:


c(a-b)=ca-cb

Then, applying this, you get:


-4(x - 2) - 3x = 2(5x - 7) + 6\\\\(-4)(x)+(-4)(-2)-3x=(2)(5x)+(2)(-7)+6\\\\-4x+8-3x=10x-14+6

Combine like terms means that you need to add the like terms.

Therefore, you get:


-7x+8=10x-8

You can observe that the expression obtained matches with the expression provided in the last option.

User AXO
by
4.6k points